2022
DOI: 10.1101/2022.02.25.481937
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An apical membrane complex controls rhoptry exocytosis and invasion in Toxoplasma

Abstract: Apicomplexan parasites possess secretory organelles called rhoptries that undergo regulated exocytosis upon contact with the host. This process is essential for the parasitic lifestyle of these pathogens and relies on an exocytic machinery sharing structural features and molecular components with free-living ciliates. Here, we performed a Tetrahymena-based transcriptomic screen to uncover novel exocytic factors in Ciliata and Apicomplexa. We identified membrane-bound proteins, named CRMPs, forming part of a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…The non-micronemal localization of RDF1 and RDF2 shown in the present work is further supported by spatial hyperLOPIT (Localization of Organelle Proteins by Isotopic Tagging) data ( Barylyuk et al, 2020 ), which demonstrated that RDF1 is part of a separate minicluster including another member of the thrombospondin family (TGME49_277910) and two multipass TM proteins (TGGT1_261080, TGGT1_292020) showing homology to the Plasmodium Cysteine-Repeat Modular Proteins ( Thompson et al, 2007 ; Douradinha et al, 2011 ). Interestingly, two recent studies deposited in a preprint repository ( Singer et al, 2022 ; Sparvoli et al, 2022 ) showed that TGGT1_261080 and TGGT1_292020 depletion impairs rhoptry discharge and that these two molecules are part of a multiprotein complex also including RDF1. These results support a model in which RDF1 and RDF2 play a key role as Coccidia-specific components of a protein complex acting as a sensor of parasite-host cell contact leading to rhoptry exocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…The non-micronemal localization of RDF1 and RDF2 shown in the present work is further supported by spatial hyperLOPIT (Localization of Organelle Proteins by Isotopic Tagging) data ( Barylyuk et al, 2020 ), which demonstrated that RDF1 is part of a separate minicluster including another member of the thrombospondin family (TGME49_277910) and two multipass TM proteins (TGGT1_261080, TGGT1_292020) showing homology to the Plasmodium Cysteine-Repeat Modular Proteins ( Thompson et al, 2007 ; Douradinha et al, 2011 ). Interestingly, two recent studies deposited in a preprint repository ( Singer et al, 2022 ; Sparvoli et al, 2022 ) showed that TGGT1_261080 and TGGT1_292020 depletion impairs rhoptry discharge and that these two molecules are part of a multiprotein complex also including RDF1. These results support a model in which RDF1 and RDF2 play a key role as Coccidia-specific components of a protein complex acting as a sensor of parasite-host cell contact leading to rhoptry exocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…The non micronemal localization of RDF1 and RDF2 shown in the present work is further supported by spatial hyperLOPIT (Localisation of Organelle Proteins by Isotopic Tagging) data (Barylyuk et al, 2020), which demonstrated that RDF1 is part of a separate minicluster including another member of the thrombospondin family (TGME49_277910) and two multipass TM proteins (TGGT1_261080, TGGT1_292020) showing homology to the Plasmodium Cysteine-Repeat Modular Proteins (Douradinha et al, 2011; Thompson et al, 2007). Interestingly, two recent studies deposited in a preprint repository (Singer et al, 2022; Sparvoli et al, 2022) showed that TGGT1_261080 and TGGT1_292020 depletion impairs rhoptry discharge and that these two molecules are part of a multiprotein complex also including RDF1. These results support a model in which RDF1 and RDF2 play a key role as Coccidia-specific components of a protein complex acting as a sensor of parasite-host cell contact leading to rhoptry exocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…The conservation of the secretion process between Apicomplexa and Alveolata is not only restricted to the membrane fusion event; it also extends to the signaling events leading to exocytosis. Recent studies in T. gondii described membrane-bound proteins, named CRMPs (cysteine repeat modular proteins), as part of a large complex essential for rhoptry secretion and invasion (109,131,133). CRMPs are conserved in Tetrahymena and required for mucocyst release (133).…”
Section: Rhoptry Exocytosis Relies On An Alveolata Conserved Machinerymentioning
confidence: 99%
“…Recent studies in T. gondii described membrane-bound proteins, named CRMPs (cysteine repeat modular proteins), as part of a large complex essential for rhoptry secretion and invasion (109,131,133). CRMPs are conserved in Tetrahymena and required for mucocyst release (133). Unlike Nd proteins, T. gondii CRMPs are not required for assembly of the RSA and are only transiently associated with the exocytic site prior to invasion (133).…”
Section: Rhoptry Exocytosis Relies On An Alveolata Conserved Machinerymentioning
confidence: 99%
See 1 more Smart Citation